Accommodating persons with sensory disabilities in South African copyright law - Nicholson, Denise Rosemary (My University, 2013)
This dissertation investigates whether the needs of persons with sensory disabilities are accommodated in South African copyright law. Of the approximately 44,8 million people in South Africa counted in Census 2001, 2,3 million were reported as disabled. Of these, 577 000 (1,3 per cent) had a visual disability, 314 000 (0,7 per cent) a hearing disability, whilst others had physical, intellectual and communication disabilities, some with multiple disabilities too. Persons with sensory disabilities, such as visual, hearing and related impairments, experience barriers to accessing information on a daily basis. The dissertation explores barriers in the copyright law and seeks ways to remedy the situation so as to facilitate access to information, particularly for educational, personal and other purposes. To contextualise this research, international and regional copyright trends are explored to establish whether intellectual property agreements allow copyright limitations and exceptions for persons with sensory disabilities in national laws. In addition, the copyright laws of a large number of countries that have already adopted appropriate limitations and exceptions nationally are reviewed. The dissertation highlights the lack of attention that the access needs of persons with sensory disabilities have been afforded in the Copyright Act 98 of 1978, as well as related inadequacies in the Electronic Communications and Transactions Act 25 of 2002. South Africa’s non-compliance with certain international and national obligations relating to human rights and access to information is also highlighted within the context of copyright law. International human rights conventions, the South African Constitution and domestic anti-discriminatory laws all provide the framework for protecting the rights of persons with disabilities, yet their rights to access to knowledge have been neglected by government and the legislature. Some recommendations for further research and possible amendments to the copyright law are provided
Keywords: Copyright law; South Africa; People with disabilities